2020
DOI: 10.1101/2020.10.23.350892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein hyperacylation links mitochondrial dysfunction with nuclear organization

Abstract: Cellular metabolism is linked to epigenetics, but the biophysical effects of metabolism on chromatin structure and implications for gene regulation remain largely unknown. Here, using a broken tricarboxylic acid (TCA) cycle and disrupted electron transport chain (ETC) exemplified by succinate dehydrogenase subunit C (SDHC) deficiency, we investigated the effects of metabolism on chromatin architecture over multiple distance scales [nucleosomes (~10^2 bp), topologically-associated domains (TADs; ~10^5 - 10^6 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 112 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…In addition to site‐specific acylations, global Kac, Kpr, Kbu, Kmal, and Ksucc of histones can weaken nucleosome stability, histone‐DNA interactions and promote nucleosome sliding. Of these modifications, Ksucc has the longest acyl‐CoA chain and imparts a negative charge, which might explain why it was able to destabilize nucleosomes to the greatest extent in an optical tweezer approach using 12‐mer nucleosomal arrays (preprint: Smestad et al , 2020). In general, single‐molecule force spectroscopy techniques, such as optical or magnetic tweezers, can be used to study the stability of clamped mononucleosomes and nucleosomal arrays by applying an accurate force and measuring motions (Fig 2C) (Neuman & Nagy, 2008).…”
Section: Introduction: Histone Lysine Acylations and Metabolismmentioning
confidence: 99%
“…In addition to site‐specific acylations, global Kac, Kpr, Kbu, Kmal, and Ksucc of histones can weaken nucleosome stability, histone‐DNA interactions and promote nucleosome sliding. Of these modifications, Ksucc has the longest acyl‐CoA chain and imparts a negative charge, which might explain why it was able to destabilize nucleosomes to the greatest extent in an optical tweezer approach using 12‐mer nucleosomal arrays (preprint: Smestad et al , 2020). In general, single‐molecule force spectroscopy techniques, such as optical or magnetic tweezers, can be used to study the stability of clamped mononucleosomes and nucleosomal arrays by applying an accurate force and measuring motions (Fig 2C) (Neuman & Nagy, 2008).…”
Section: Introduction: Histone Lysine Acylations and Metabolismmentioning
confidence: 99%
“…A cellular function study of Sirt7 revealed that the Sirt7-catalyzed desuccinylation of H3K122 promoted chromatin condensation and DNA-damage repair ( Li et al, 2016 ). Moreover, metabolically driven hypersuccinylation of histones was reported to weaken nucleosome stability ( Smestad et al, 2020 ), further underlining the general effects of lysine succinylation on nucleosome dynamics.…”
Section: Role Of Lysine Succinylationmentioning
confidence: 99%